Implementasi Agile Pengembangan Sistem Informasi Karyawan Berbasis Next.Js dan PostgreSQL: Studi Kasus Yayasan Almadani - Sasongko, Agung; Lailiah, Badariatul; Hadikusumah, Prima Surya; Marien, Yunita (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2025)
This research aims to develop a web-based employee information system for Almadani Syarif Abdurrahman Pontianak Foundation to improve the efficiency of employee data management and facilitate access to employee-related documents. The system was developed using Agile methodology, which enables an adaptive development process through sprint cycles. The Next.js framework was used to improving interface speed, while PostgreSQL was chosen as the database to ensure data integrity and security. Testing results through User Feedback at 9 sprints showed a gradual increase in user satisfaction. The average user assessment scores for key modules, such as employee data management, showed a steady improvement with adjustments made after each sprint, resulting in an average score of 4.14 out of 5. The burn-down diagram showed work progress consistent with the target time, indicating that the development team managed to effectively reduce the backlog until the project was completed on schedule in 45 days. User Acceptance Testing (UAT) revealed high satisfaction levels: 90% for design, 92.5% for ease of use, and 89% for efficiency. System page caching reduced access times by 60-80%, especially on pages with large data loads. Overall, the developed system successfully improved administrative efficiency and streamlined employee data search and management processes.